Retention in statutory social work from fast-track child and family programs - Scourfield, Jonathan; Carpenter, John; Warner, Nell; Maxwell, Nina; Venn, Laura; Stepanova, Evgenia; O’Donnell, Chloe; Jones, Rebecca; Elliott, Martin; Smith, Roger (Journal of Social Work, 2023)
Summary: Two fast-track child and family social work training programs have been established in England — Step Up to Social Work and Frontline. Trainees’ financial support is far higher than for mainstream social work degrees. One of the reasons claimed for setting up these programs is addressing retention, although critics (of Frontline) predicted graduates would not stay in social work. A 4-year study assessed retention and reasons for leaving social work. Attrition rates from statutory social work were calculated from responses (n = 2543) to annual surveys, plus looking up non-respondents in the professional register. Interviews were conducted with fast-track graduates (n = 80) and employers (n = 29). Findings: The overall rate of social work graduates not in statutory social work at 18 months post-qualification was 12% for fast-track programs, and Higher Education Statistics Agency survey data show attrition at 15 months post-qualification as 18% for all social work routes. Frontline's original national recruitment approach was less successful for retention than Step Up to Social Work's regional approach. Perceived local authority support and intrinsic job satisfaction were associated with attrition in longitudinal bivariate analysis. Fast-track graduates leaving statutory social work typically moved to work in social care (including policy roles), health, or education. Applications: Early-career attrition appears to be somewhat lower from fast-track programs than from all social work graduates. Longer-term comparison is not yet possible. In promoting retention, employers should be aware of the importance of staff perceptions of the local authority as supportive, and of their intrinsic job satisfaction.